Bartonellosis and pregnancy: Report of a case - Campos, Sonia (2015)
Bartonellosis a case of pregnancy in eruptive phase, confirmed by immunological studies and pathological diagnosis is presented. It was a woman of 37 weeks primigravida was admitted with sporadic uterine contractions and papuloeritematosa trombocitopemia eruption. Had history of travel to endemic area five months earlier, then had fever for two weeks. The liver was 3 cm and spleen at 5 cm below costal margin. He studied with hypertension and treatment began with alpha-methyldopa 1 g every 12 h. platelets decreased to 29 000, DHL, 496, and traces of albuminaria. Cesarean section was performed by hypertensive disease of pregnancy and trombocitopemia, women with newborn of 1970 g and Apgar 8. Postoperatively there was rapid remission of hypertension. Skin biopsy was compatible with Peruvian wart, the outcome was favorable. A review of the literature is made.